Surgical Correction of Ascending Aortic Aneurysm Without Coronary Dilatation After Kawasaki Disease in a 3-Year-Old Child - Santos,Rômullo M (2022)
Abstract Kawasaki disease (KD) is an inflammatory condition that may affect genetically predisposed individuals in pediatric ages after infectious/environmental triggering. An infrequent finding associated with KD is ascending aortic aneurysm during or after the acute phase of the disease. In this Multimedia presentation, we describe a three-year-old girl submitted to surgical treatment.